Mu'adalah Education Transformation in Al-Abror Boarding School, Tapanuli Selatan District - Asari, Hasan; Kenny Agusto Arie Wibowo; Ahyar, Saiful; Zainal Abidin; Aswan (EDUTEC : Journal of Education And Technology, 2023)
This study examines the educational transformation of Mu'adalah using qualitative research methods, with data collection techniques using interviews, observation and documentation. The results of the study show that the modernization pattern of mu'is education is at the Al-Abror Islamic Boarding School, South Tapanuli Regency. The pattern in this Islamic boarding school adheres to two aspects, namely based on the education and teaching system and based on the Kulliyatul Mu'allimin al-Islamiyah (KMI) Curriculum. The references to the two aspects of modernization in this pesantren are aimed at the modern Pondok Gontor Ponorogo Indonesia (KH. Imam Zarkasyi, KH, Ahmad Sahal and KH. Zainudin Fananie, namely the Trimurti Pondok Modern Gontor Ponorogo Indonesia). The educational method taught in Islamic boarding schools includes three elements, namely intra-curricular, extra-curricular and co-curricular curriculum elements. From the elements of the intra-curricular curriculum, the mu'ada transformation at the al-Abror Islamic boarding school includes العلوم الاسلامية , العلوم اللغوية, العلوم العامة. Then from the co-curricular elements it includes three namely the development of lughowiyah, amaliyah of worship and development of science and technology,